Duha Prayer in Building Religious Habits among Madrasah Ibtidaiyah Students - Nadila Ristiani; S Sutama (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This article has three research objectives. 1) To describe the procedure of wudhu (ablution) before Duha prayer in building religious habits among elementary school students. 2) To describe the implementation of Duha prayer in building religious habits among elementary school students. 3) To explore the practice of prayer after Duha prayer in building religious habits.Methodology: This study used a qualitative-ethnographic approach. Data collection was conducted through interviews, observations, and document analysis.Results: The results show that students perform ablution procedures in accordance with Islamic law. These ablution procedures serve as a means of instilling religious values. The routine practice of Duha prayer instills discipline and devotion in students and builds religious habits. The practice of prayer after Duha prayer has an impact on strengthening spiritual awareness. These religious habits can grow through consistent and meaningful prayer practicesApplications/Originality/Value: This study shows that wudhu, regular Duha prayers, and prayers after salat are effective in building discipline, devotion, and spiritual awareness in students. These findings provide practical guidance for teachers and schools in consistently instilling religious values, as well as adding to the understanding of the direct relationship between daily worship practices and the formation of religious habits in children.